An analysis of adoption of blockchain technology in the private banking sector of Bangladesh - Saha, Khokan Kanti (Brac University, 2021)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2021.